Human-to-Human Transmission of Influenza A(H3N2) Virus with Reduced Susceptibility to Baloxavir, Japan, February 2019 - Takashita, Emi; Ichikawa, Masataka; Morita, Hiroko; Ogawa, Rie; Fujisaki, Seiichiro; Shirakura, Masayuki; Miura, Hideka; Nakamura, Kazuya; Kishida, Noriko; Kuwahara, Tomoko; Sugawara, Hiromi; Sato, Aya; et al. (Emerging infectious diseases, 2019)
In 2019, influenza A(H3N2) viruses carrying an I38T substitution in the polymerase acidic gene, which confers reduced susceptibility to baloxavir, were detected in Japan in an infant without baloxavir exposure and a baloxavir-treated sibling. These viruses' whole-genome sequences were identical, indicating human-to-human transmission. Influenza virus isolates should be monitored for baloxavir susceptibility.